The Lesson Observation for the Productive Learning Environment in English Classes: Stories from Two Elementary Schools - Bunga Ayu Wulandari; Syahrial Syahrial; Andari Amalia Syahrial; Yundi Fitrah (Universitas Jambi, Indonesia, 2022)
In Indonesia, English is not required for the elementary school students in the current curriculum. This qualitative case study examines the role of teachers in providing a productive learning environment through classroom activities in English classes at two elementary schools in Jambi, a province in Indonesia.. The productive learning environment is characterised by target-oriented, genuine and real-based learning, encouraging and appealing activities, dynamic and accommodating knowledge formation, autonomous, and contemplative. The data were gathered from observations in 7 classes and teacher interviews. This research revealed that there was not a single meeting that altogether covered the six features of a productive learning environment. Therefore, it is suggested that teachers should understand more about a productive learning environment to empower classroom activities to help students achieve educational goals.